Significance of nuclear p-mTOR expression in advanced oral squamous cell carcinoma with extracapsular extension of lymph node metastases. Issue 5 (May 2015) - Chen, Tseng-Cheng; Wu, Chen-Tu; Wang, Cheng-Ping; Yang, Tsung-Lin; Lou, Pei-Jen; Ko, Jenq-Yuh; Chang, Yih-Leong
Summary Objectives Traditional dichotomous extranodal extension (ENE) grading could not differentiate the risk of subsequent failure in advanced stage oral squamous cell carcinoma (OSCC) patients with ENE. This study investigated nuclear phosphorylated mammalian target of rapamycin (p-mTOR) expression in extranodal tumours and correlated this with clinical outcomes. Materials and methods A total of 218 advanced stage OSCC patients with neck lymph node metastasis were enrolled. Paired paraffin-embedded primary tumour and metastatic lymph node sections were stained with antibody against p-mTOR. Tumours with moderate-to-strong staining in ≧50% of tumour cells were recorded as being positive p-mTOR expression. The correlation of nuclear p-mTOR expression in extranodal tumours with clinicopathologic parameters was analysed. Results Nuclear p-mTOR expression in primary and extranodal tumours was highly associated with a lower grade of differentiation. The 5-year disease-free survival (DFS) of the patients without ENE, with and without positive nuclear p-mTOR expression in extranodal tumours was 54.3%, 23.4% and 55.2%, respectively. The 5-year overall survival (OS) of the patients without ENE, with and without nuclear p-mTOR expression in extranodal tumours was 55%, 18.7% and 51.3%, respectively. The patients with nuclear p-mTOR expression in extranodal tumours had significantly worse regional and distant disease control. Multivariate analysis also confirmed that nuclear p-mTOR expression in extranodal tumours was a significant independent adverse factor. Conclusion Nuclear p-mTOR expression can be used as a prognostic indicator predictive of DFS and OS in advanced OSCC patients with ENE. There might be a possibility for targeted therapy in this group of patients.